CHALLENGES OF TOURISM CAMPAIGNS IN THE NEW NORMAL ERA: ANALYSIS ON INDONESIAN GOVERNMENT'S SOCIAL MEDIA - Dimas Subekti (Profetik: Jurnal Komunikasi, 2022)
The COVID-19 pandemic has had a severe impact on the tourism industry sector. The government is trying to revive the Indonesian tourism sector by issuing a new normal policy.Therefore, this study aims to determine how Twitter is used as a tourism campaign tool by the Indonesian government in the new normal era of the COVID-19 pandemic. This study uses a descriptive qualitative approach to explain the tourism campaign in the new normal era of the COVID-10 pandemic by the Indonesian government through Twitter social media. This study uses the NVIVO 12 Plus analysis technique with chart features, word frequency, and cluster analysis. The source of this research data is the Twitter account of the Ministry of tourism and creative economy and the charm of Indonesia. The findings in this study are the Twitter content of the Ministry of tourism and creative economy and the charm of Indonesia in campaigning for Indonesian tourism is about tourist facilities, tourist events, tourist destinations, and health protocol. The narrative of the Twitter account of the Ministry of Tourism and Creative Economy and Indonesian charm is related to invitations to travel to Indonesia, the beauty of tourism, and Indonesian tourist destinations. Actors involved in the Indonesian tourism campaign are Minister Sandiaga Salahudin Uno and Deputy Minister Angela Tanoesoedibjo, and President Joko Widodo. The two Twitter accounts have a balanced intensity in campaigning for Indonesian tourism from July 2020 to June 2021.